OVERVIEW OF PARENTS' PARENTING PATTERNS ON TOOLS AGED BY THE COVID-19 PANDEMIC AT PAUD IRSYADUS SALAM MEGALUH JOMBANG - Muzayyaroh Muzayyaroh; Siti Roudhotul Jannah; Dewi Triloka Wulandari; Dian Puspita Yani; Sribanun Titi Istiqomah (Media Bina Ilmiah, 2023)
Background : This COVID-19 pandemic situation causes children and most of the parents to spend time at home to avoid crowds for the safety of themselves and their families. The government recommends that all activities be carried out from home, such as work and study. For this reason, parents are required to be able to guide and facilitate all children's needs to ensure children can learn and develop well, so parenting during this pandemic is an important thing that parents must pay attention to. This research aims to find out the description of parenting styles for toddlers during the Covid-19 pandemic at PAUD Irsyadus Salam Megaluh Jombang. Method: Descriptive method with data collection through filling out a questionnaire. The population in this study were all mothers of children under five who attended PAUD Irsyadus Salam with a total of 30 mothers. Sampling by non-probability sampling with purposive sampling type. Results : Most parents are authoritarian towards their children where all decisions are taken by the parents themselves without any discussion with the child. Conclusion : The authoritarian attitude of parents to children is due to the implementation of learning during the Covid-19 emergency which is carried out online which requires parents to take over the learning process. Supposedly, the authoritarian parenting pattern is changed to a democratic parenting pattern where parents provide opportunities and listen to children's opinions, direct and respect and apply standards of behavior clearly while recognizing the important needs of children. That way the relationship between children and parents can be established well